Optimizing battery safety and performance: Hardware implementation and simulation analysis of protective measures, SoC Measurement, and cell balancing in BMS - Atul Kumar Singh; C. P. Boopathy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
This paper presents a dual-platform validation of a compact battery management system (BMS) combining an Arduino-based hardware prototype and a MATLAB/Simulink model for cross-validation. The hardware implements over-voltage, over-current, and over-temperature protections, state of charge (SOC) estimation using open-circuit voltage (OCV) and coulomb counting (CC), and both passive and active balancing. Experimental results show that SOC accuracy remains within ±2%, active balancing achieves 57% higher energy efficiency and 37% faster convergence than passive balancing, and thermal rise is limited to <5 °C. Limitations include fixed protection thresholds and the absence of physical validation of long-term aging effects. The dual-platform approach allows cross-validation of hardware and simulation, benchmarking SOC estimation methods, and quantifying energy and thermal trade-offs between balancing strategies. This approach offers a low-cost and reproducible validation pathway for EV-oriented BMS design.